1991
DOI: 10.1093/oxfordjournals.aje.a115964
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Ectopic Pregnancy: A Case-Control Study in France, with Special Focus on Infectious Factors

Abstract: A case-control study was conducted in 1988 in seven Paris area maternity hospitals to evaluate the role of several risk factors, particularly infectious factors, in ectopic pregnancy. A total of 279 cases and 279 controls were compared for sociodemographic characteristics, cigarette smoking, sexual, reproductive and surgical histories, and conditions of conception. Pelvic inflammatory disease confirmed by celioscopy (odds ratio (OR) = 5.5, 95% confidence interval (CI) 2.1-13.9) and Chlamydia trachomatis seropo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
49
2
3

Year Published

1998
1998
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(59 citation statements)
references
References 0 publications
5
49
2
3
Order By: Relevance
“…The studies conducted by Handler A et al(1989) [7], Coste J et al(1991) [8] and Bouyer J et al(2003)[9] has showed that history of smoking was present in 38.30%, 40.14% and 58.53% cases respectively which was not comparable to the present study. This could be attributed to regional and socio-economic factors.…”
Section: Discussioncontrasting
confidence: 93%
“…The studies conducted by Handler A et al(1989) [7], Coste J et al(1991) [8] and Bouyer J et al(2003)[9] has showed that history of smoking was present in 38.30%, 40.14% and 58.53% cases respectively which was not comparable to the present study. This could be attributed to regional and socio-economic factors.…”
Section: Discussioncontrasting
confidence: 93%
“…Also, ectopic pregnancy causes serious reductions in subsequent fertility, with a 20% chance of recurrence and a 20% to 40% chance of definitive infertility.3 Several ectopic pregnancy risk factors have been identified, including pelvic inflammatory disease, smoking at the time of conception, pelvic surgery, previous use of an intrauterine device, and induced ovulation. 6 Current use of an intrauterine device is also associated with ectopic pregnancy, because it lowers the risk of uterine pregnancy more than the risk of ectopic pregnancy.3 In a French study, these factors, in combination, explained approximately 65% of all ectopic pregnancies,9 suggesting that about one third of ectopic pregnancies occur in women with no identified risk factors. In the framework of research on other f risk factors, we investigated the role of previous reproductive outcomes (previous ectopic pregnancy and pervious spontaneous and induced abortions) in terms of the risk of subsequent ectopic pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…Ectopic pregnancy may have serious consequences, in particular by impairing subsequent fertility (2,3). Several risk factors have been identified (infectious pelvic disease, smoking, tuba1 surgery, induced conception, age) (2,(4)(5)(6)(7), but the etiology of one-third of the cases of ectopic pregnancy remains unknown (7).…”
mentioning
confidence: 99%